The Impact of the Open Proportional System Decision on Democracy and Political Stability in the 2024 General Election - Moch Oghin Hegar Al Hamar; Ahmad Hunaeni Zulkarnaen; Dedi Mulyadi; Saptaning Ruju Paminto (Yayasan Studi Cendekia Indonesia (YSCI), 2024)
The open proportional electoral system implemented in Indonesia since the 2009 general election aims to improve political representation and strengthen democracy by giving voters more freedom to directly select legislative candidates. However, despite its good intentions, the system presents various challenges in practice, including high political costs, rampant money politics, and weak party control over legislative candidates. The main issue in this research is how the effectiveness of the open proportional system in achieving the goal of fair and stable political representation in Indonesia. This research uses a normative juridical approach to analyse the Constitutional Court's decisions related to the electoral system, as well as comparing with other electoral systems. The author argues that although an open proportional system can increase voter freedom, its negative impacts are greater, especially in terms of high political costs and money politics practices that undermine the integrity of elections. In addition, this system causes divisions within political parties, as legislative candidates focus more on personal votes rather than the collective interests of the party. The findings of this study suggest that although an open proportional system is more democratic in theory, its implementation in Indonesia tends to exacerbate political inequality and reduce political stability. Therefore, a mixed proportional system is suggested as a more effective solution to improve political representation and reduce the negative impacts.